2020
DOI: 10.1155/2020/6627472
|View full text |Cite
|
Sign up to set email alerts
|

The Prevalence and Determinants of Hand and Face Dermatitis during COVID-19 Pandemic: A Population-Based Survey

Abstract: Background. During the current COVID-19 pandemic, prevention is the key to limiting the spread of this disease. The frequent handwashing and use of sanitizers resulted in notable skin changes among some individuals. The aim of the study was to determine the prevalence and determinants of the new onset of dermatitis during the COVID-19 pandemic in a university population from Saudi Arabia. Methods. A cross-sectional study was conducted using a self-administered online questionnaire by sending an invitation link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
39
1
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 30 publications
(50 citation statements)
references
References 35 publications
(39 reference statements)
4
39
1
1
Order By: Relevance
“…The media prevalence of skin side events related to mask use was 57.17% after conducting a random effect meta-analysis weighted by the study sample size, Figure S2. Eleven studies Accepted Article evaluated the skin effects related to mask wearing [21][22][23][24][25][26][27][28][29][30][31] . Four studies analyzed the overall prevalence of skin side events related to mask wearing [21][22][23][24] , Table 2.…”
Section: What Is the Prevalence And What Kind Of Side Events Are Related To Mask Use?mentioning
confidence: 99%
See 4 more Smart Citations
“…The media prevalence of skin side events related to mask use was 57.17% after conducting a random effect meta-analysis weighted by the study sample size, Figure S2. Eleven studies Accepted Article evaluated the skin effects related to mask wearing [21][22][23][24][25][26][27][28][29][30][31] . Four studies analyzed the overall prevalence of skin side events related to mask wearing [21][22][23][24] , Table 2.…”
Section: What Is the Prevalence And What Kind Of Side Events Are Related To Mask Use?mentioning
confidence: 99%
“…Longer periods of mask wearing were a risk factor for skin adverse events 21,32 , while controversial results were found regarding the type of mask. Most reports observed that wearing a surgical mask was a risk factor for developing skin side events compared to other kind of mask 21,23,24 . Nevertheless, Matusiak et al showed that surgical mask was a protective factor for sweating and itch 32 .…”
Section: What Is the Prevalence And What Kind Of Side Events Are Related To Mask Use?mentioning
confidence: 99%
See 3 more Smart Citations